2018
DOI: 10.2147/opth.s158403
|View full text |Cite
|
Sign up to set email alerts
|

A multicenter retrospective comparison of goniotomy versus trabecular bypass device implantation in glaucoma patients undergoing cataract extraction

Abstract: PurposeThe aim of this study was to compare intraocular pressure (IOP) outcomes in eyes with cataract and glaucoma undergoing phacoemulsification (phaco) in combination with goniotomy using the Kahook Dual Blade (KDB) or implantation of a single iStent trabecular bypass device.MethodsRetrospective analysis of IOP and IOP-lowering medication reduction in eyes undergoing phaco-goniotomy with KDB (n=237) or phaco-iStent (n=198). Preoperative, intraoperative, and postoperative data were collected through 6 months … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
60
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(68 citation statements)
references
References 10 publications
6
60
2
Order By: Relevance
“…The retrospective nature of data collection is a limitation of the study; the risk of selection bias was mitigated by including data from all Latino subjects undergoing the procedure within the data collection window. The lack of a control group is also a limitation that precludes benchmarking these outcomes against other procedures, although the similarity of the results in this series to published results of other studies—including comparative studies 16 , 18 , 20 , 21 , 25 , 26 supports the representative nature of these data. Also, as this was a retrospective study, there was no specific protocol for the addition or withdrawal of medications; instead, these decisions were made by the investigator on a case by case basis determined by clinical status, as reflects clinical practice.…”
Section: Discussionsupporting
confidence: 59%
“…The retrospective nature of data collection is a limitation of the study; the risk of selection bias was mitigated by including data from all Latino subjects undergoing the procedure within the data collection window. The lack of a control group is also a limitation that precludes benchmarking these outcomes against other procedures, although the similarity of the results in this series to published results of other studies—including comparative studies 16 , 18 , 20 , 21 , 25 , 26 supports the representative nature of these data. Also, as this was a retrospective study, there was no specific protocol for the addition or withdrawal of medications; instead, these decisions were made by the investigator on a case by case basis determined by clinical status, as reflects clinical practice.…”
Section: Discussionsupporting
confidence: 59%
“…50% of the iStent price. Studies comparing the efficacy of the iStent treatment and KDB goniotomy (both procedures performed in conjunction with cataract phacoemulsification) showed that the degree of IOP reduction was similar for both modalities [37] or KDB goniotomy was superior to a single iStent [38,39].…”
Section: Discussionmentioning
confidence: 99%
“…The tissue to be excised is lifted on an appropriately profiled ramp and removed from its original position, so that it can be removed from the eye after the procedure is completed. Such controlled excision of the trabecular meshwork establishes a direct connection of the anterior chamber with Schlemm's canal and then communication with the aqueous veins [10,11]. Through this sequence, the procedure increases the aqueous humor outflow via the conventional pathway.…”
Section: Introductionmentioning
confidence: 99%
“…In a study of 42 eyes of 24 subjects with angle closure glaucoma undergoing phacoemulsification and KDBassisted goniosynechialysis and excisional goniotomy, 6 months of follow-up demonstrated mean IOP reductions of 10.1-12.8 mmHg (38.4-49.5%; P < 0.0001) [23]. At 6 months, 92.9% of eyes achieved IOP ≤ 18 mmHg, all eyes achieved IOP reduction of ≥ 20%, and 85.7% were medication-free [24]. Although there was no comparison to cataract surgery alone, their findings suggest that goniosynechialysis and excisional goniotomy with the KDB together with cataract extraction may play a helpful role in optimizing outflow and IOP reduction in angle closure glaucoma eyes.…”
Section: Kahook Dual Bladementioning
confidence: 96%
“…Two recent studies compared the efficacy of goniotomy with the KDB to iStent implantation in glaucoma patients undergoing cataract surgery. In a retrospective multicenter comparison of 237 eyes undergoing KDB goniotomy with phacoemulsification and 198 eyes undergoing iStent implantation with phacoemulsification, authors reported that those in the KDB group had a significantly greater IOP reduction (− 4.2 mmHg, 23.7%) compared to the iStent implantation and phacoemulsification group (− 2.7 mmHg, 16.4%, P < 0.001) after six months of follow-up in eyes with mild to moderate glaucoma [24].…”
Section: Comparative Studiesmentioning
confidence: 99%